2015
DOI: 10.1016/j.ifacol.2015.05.141
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete/Continuous Numerical Approach to Multi-physics

Abstract: A variety of technical applications are not only the physics of a single domain, but include several physical phenomena, and therefore are referred to as multi-physics. As long as the phenomena being taken into account is either continuous or discrete i.e. Euler or Lagrangian a homogeneous solution concept can be employed. However, numerous challenges in engineering include continuous and discrete phase simultaneously, and therefore cannot be solved only by continuous or discrete approaches. Problems include b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further validation studies on drying in particular for moving beds are to be found in refs. [45][46][47].…”
Section: Drying and Coke Combustionmentioning
confidence: 99%
“…Further validation studies on drying in particular for moving beds are to be found in refs. [45][46][47].…”
Section: Drying and Coke Combustionmentioning
confidence: 99%
“…The void fraction in fixed bed reactors is not uniform and varies from the vicinity of the walls toward the bulk of the bed, and it needs to be incorporated into the model to also consider the wall effects. The XDEM has the ability to provide porosity distribution inside the flow field by considering the position and number of particles in each CFD cell . This advantage eliminates the need for correlations to calculate porosity distribution, and as a consequence, it predicts the fluid properties such as velocity and volume fraction in a more accurate and precise way.…”
Section: Mathematical Model and Numerical Solutionmentioning
confidence: 99%
“…The XDEM has the ability to provide porosity distribution inside the flow field by considering the position and number of particles in each CFD cell. 30 This advantage eliminates the need for correlations to calculate porosity distribution, and as a consequence, it predicts the fluid properties such as velocity and volume fraction in a more accurate and precise way. The porosity calculation algorithm is based on the method proposed by Xiao et al, 31 which considers that the volume of each particle is distributed to all the neighbor cells according to its distance to the cell centers.…”
Section: Solutionmentioning
confidence: 99%